Interactive multimedia learning arithmetic and IQ / Mohd Nizam Ayub - Mohd Nizam , Ayub (2002)
One of the most rapidly changing and exiting areas of education today is the development of computer based learning materials, especially interactive multimedia program that run on personal computer. These new technologies offer children, student and other people access to materials as never before Through the condensed storage capabilities of computer, multimedia can deliver large amount of information in the ways that make it manageable, approachable and useful. And by making it possible to access illustration and photographs, sound and video, as well as large amount of text, interactive multimedia program present learning arithmetic and IQ test to children in newly engaging and meaningful way. This Interactive Multimedia Learning Arithmetic and IQ are for children between 8 to 12 years old. This report focuses on developing the arithmetic skills and IQ knowledge for the children. There are two phases in this package, that is learning arithmetic and IQ knowledge for the children. The ·waterfall model' was selected for the development process because it supports rapid application development and reduces the risks involves. Software engineering principles based on this methodology were applied throughout the development phase.